Does Religious Commitment Influence Takaful Participation - Hartini, Ab Ghani; Salman, Lambak; Sofiah, Abd Rahman; Mustafa, Dakian (2016)
Malaysia is a multicultural country with Islam as the major religion. With a population over 30 million as at 2016 and 61% are Muslims, Takaful (Islamic insurance) has significant potentials for growth. Nonetheless, even after its introduction in Malaysia, 30 years ago, its penetration rate is still low with only 14.71% as compared to conventional of 55%. Past studies in the area of Islamic financial instruments suggest that religious commitment, attitude and perceived behaviour are critical descriptors of participation intention. However, the role of religious commitments has so far met with mixed results. This study, thus, carried out to further examine the influence of religious commitment toward Takaful participation intention. A sample of 500 respondents classified as professional were taken from three cities of Malaysia to examine whether religious commitment influence the intention to participate in Takaful. Data for this study were collected via a self-administered questionnaire containing five sections where section A contains multiple choice questions and the rest of the sections; section B-E were Likert scale questions which were developed using past validated instruments with changes to make them more relevant to this study. Data was analysed using multiple regression with SSPS version 20. The study found that religious commitment has the strongest influence to the Takaful participation. The paper has practical significance for Takaful policy makers in their marketing strategy as understanding consumer behaviour is crucial.